A Systematic Review of Risk Factors Associated with Near-Fatal and Fatal Asthma. Issue 5 (3rd August 2005) - Alvarez, GG; Schulzer, M; Jung, D; FitzGerald, JM
Abstract : BACKGROUND: Asthma mortality and morbidity continue to be a serious global problem. Systematic reviews provide an opportunity to review risk factors in detail. OBJECTIVE: To review all of the literature for risk factors associated with near-fatal asthma (NFA) and fatal asthma (FA). METHODS: A literature search from 1960 to January 2004 in MEDLINE and EMBASE was conducted. Studies were included based on the following criteria: NFA was defined as an asthma exacerbation resulting in respiratory arrest requiring mechanical ventilation or a partial pressure of CO2 of at least 45 mmHg or asthma resulting in death (FA); the study reported the number of cases (NFA and/or FA) and asthmatic controls; there was explicit reporting of risk factors; cases that were adult and pediatric in nature; and all study types. Studies that included patients with chronic obstructive pulmonary disease were excluded. RESULTS: Four hundred and three articles were identified, of which 27 met the inclusion criteria. Increased use of medications such as beta-agonists via metered dose inhalers (OR=1.67, 95% CI 0.99 to 2.84, P=0.057) and nebulizers (OR=2.45, 95% CI 1.52 to 3.93, P=0.0002), oral steroids (OR=2.71, 95% CI 1.34 to 5.51, P=0.006) and oral theophylline (OR=2.02, 95% CI 1.03 to 3.98, P=0.04) and a history of hospital (OR=2.62, 95% CI 1.04 to 6.58, P=0.04) and/or intensive care unit (OR=5.14, 95% CI 1.91 to 13.86, P=0.001) admissions and mechanical ventilation (OR=6.69, 95% CI 2.80 to 15.97, P=0.0001) due to asthma were predictors of NFA and FA. Prior emergency department assessment did not confer a greater risk of NFA and FA (OR=1.13, 95% CI 0.43 to 2.92, P=0.810).The use of inhaled corticosteroids (ICS) measured in a dose-independent fashion (did the patient take ICS previously; yes or no) inferred equivocal risk of NFA and FA (OR=1.31, 95% CI 0.83 to 2.05, P=0.25). However, two studies measured the use of ICS in a dose-dependent fashion (ie, measured the number of prescriptions filled within the previous six to 12 months). Both studies showed a trend toward a protective effect against FA. One study showed that the premature cessation of ICS can hasten death. CONCLUSIONS: In the present study, risk factors of NFA and FA have been more accurately defined. Clinicians should identify patients with these characteristics to reduce their risk of NFA and FA. Further research should focus on quantifying the impact of risk factors on asthma deaths.